Haemoglobinopathies in Referred Cases for Haemoglobin Electrophoresis in a Tertiary Care Teaching Hospital - Maha Tariq, Maha Tariq; Qandeel Zafar, Qandeel Zafar; Warda Waheed, Warda Waheed; Atifa Shuaib, Atifa Shuaib; Javeria Qaiser, Javeria Qaiser; Muhammad Nauman Malik, Muhammad Nauman Malik (Students’ Supplement of Journal of Rawalpindi Medical College, 2019)
Background: Haemoglobinopathies can be quantitative (thalassemic syndromes) or qualitative (Hb variants). Haemoglobinopathies are the most common genetic defect globally. The rationale of this study is to evaluate the distribution of haemoglobinopathies in Pakistani population. The objective of this study is to determine the frequencies of different haemoglobinopathies in all the referred cases for haemoglobin electrophoresis of a tertiary care teaching hospital. Methods And Materials: A descriptive cross sectional study was conducted in the department of haematology, Holy Family Hospital, Rawalpindi. Two thousand and five cases referred for haemoglobin electrophoresis from September 2016 to June 2017 were included in the study using nonprobability consecutive sampling. Data regarding patient’s age, gender, registration number, red cell indices, hemoglobin and Hb electrophoresis were collected through files of the data office. SPSS 22 was used to analyse the data, descriptive statistics were calculated. Results: Out of 2005 cases, 1934 (96.5%) were females and 70 (3.5%) were males. Age was ranging from 1-55 years with a mean age of 26.38±5.71 years. Haemoglobinopathies were found in 87 (4.34%) patients. The commonest haemoglobinopathy found was HbD trait 44 (2.2%) followed by beta thalssaemia trait 29 (1.4%), HbJ/HbI 6 (0.3%), beta thalassaemia major 3 (0.1%), sickle cell trait 2 (0.1%), thalassaemia intermedia 1 (.0%), homozygous HbD disease 1 (.0%) and HbE trait 1 (.0%). Mean Hb(g/l), RBCs (x10^12/l), MCV (fl), MCH (pg) and RDW-SD were 9.22±3.08, 3.94±0.77, 75.18±11.04, 23.53±4.55 and 46.52±8.00 respectively. Conclusion: 4.34% of 2005 cases referred for haemoglobinopathy evaluation had haemoglobinopathy. HbD trait (55%) and beta thalassemia trait (33.3%) were commonest haemoglobinopathies. Keywords: haemoglobinopathies, thalassaemia, haemoglobin variants, haemoglobin electrophoresis.